A new, but possibly extinct, species of Semanopterus Hope, 1847 from Lord Howe Island, in the southwestern Pacific Ocean (Coleoptera: Scarabaeidae: Dynastinae) - Reid, Chris A.m.; Tees, Natalie A. (Zootaxa, 2023)
A new and brachypterous species of Semanopterus Hope, 1847 (Coleoptera: Scarabaeidae: Dynastinae: Pentodontini) is described: S. kingstoni Reid & Tees, new species. The species is based on a single female specimen, collected on Lord Howe Island in the southwest Pacific Ocean. It is the sixth species of dynastine known from Lord Howe Island; a key is provided for identification of all of the species known from this small island.